Female-to-male sex reversal associated with unique Xp21.2 deletion disrupting genomic regulatory architecture of the dosage-sensitive sex reversal region. Issue 10 (8th May 2017) - Dangle, Pankaj; Touzon, María Sol; Reyes-Múgica, Miguel; Witchel, Selma F; Rajkovic, Aleksandar; Schneck, Francis X; Yatsenko, Svetlana A
Abstract : Background: The XX male disorder of sex development (DSD) is a rare condition that is most commonly associated with the presence of the SRY gene on one of the X chromosomes due to unequal crossing-over between sex chromosomes during spermatogenesis. However, in about 20% of the XX male individuals, SRY is missing, although these persons have at least some testis differentiation. The genetic basis of genital ambiguity and the mechanisms triggering testis development in such patients remain unknown. Methods: The proband with 46, XX SRY -negative testicular DSD was screened for point mutations by whole exome sequencing and CNVs using a high-resolution DSD gene-targeted and whole genome array comparative genomic hybridisation. The identified Xp21.2 genomic alteration was further characterised by direct sequencing of the breakpoint junctions and bioinformatics analysis. Results: A unique, 80 kb microdeletion removing the regulatory sequences and the NR0B1 gene was detected by microarray analysis. This deletion disturbs the human-specific genomic architecture of the Xp21.2 dosage-sensitive sex (DSS) reversal region in the XX patient with male-appearing ambiguous genitalia and ovotestis. Conclusions: Duplication of the DSS region containing the MAGEB and NR0B1 genes has been implicated in testis repression and sex reversal. Identification of this microdeletion highlights the importance of genomic integrity in the regulation and interaction of sex determining genes during gonadal development.